(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2020)
Background: Organophosphate Compound (OPC) poisoning is common following either intentional or accidental exposures. Many parameters are proposed to predict outcome. Considering the lack of information in this regard in our setting this study was performed to investigate the role of Peradeniya Organophosphorus Poisoning (POP) scale as a prognostic marker in OPC poisoning in a tertiary care hospital of Bangladesh. Materials and methods: This prospective observational study was conducted in the Department of Medicine, Chittagong Medical College Hospital, Chattogram. One hundred consecutive patients above 12 years of age with acute OPC poisoning were selected and POP score was assessed. Patients were followed up till discharge or death (Which was earlier) to observe the outcome. Results: Mean age was 27.2 ± 9.5 (Range: 13-75) years and 58% were male. On admission, as per the POP score, 61% had mild, 32% had moderate and 7% had severe grades of poisoning. The severe group had a significantly higher need for ventilator support (71.4%) and death (42.3%) which progressively declined in the moderate and mild group. Total atropine dose and length of hospital stay was significantly associated with clinical POP scale score. Conclusions: We conclude that the POP score can be used for severity assessment and prognostication of OPC poisoning cases at the time of presentation in a resource limited country like Bangladesh. JCMCTA 2020 ; 31 (2) : 110-114